IJCM_239A: Health seeking behaviour and its determinants among adult population: a comparative study between urban and rural area of western Uttar Pradesh - Sulthana Banisha; Gautam Neelam S; Bano Tanveer (Wolters Kluwer Medknow Publications, 2024)
Background: Health seeking behaviour is remedial action undertaken by individuals for their health problem or illness. It may vary in rural and urban areas and with different sociodemographic variables. To provide adequate health care services to the community, it is essential to know about their health seeking behaviour and its determinants. Objectives: 1. To describe health seeking behaviour and determine various factors influencing it among adult population in rural and urban areas of Meerut. 2. To assess their awareness on health insurance policies. Methodology: A community based cross-sectional study among adult population was conducted in rural and urban areas of Meerut, Uttar Pradesh from 1st July to 30th September, 2023. Estimated sample size was 200 each from rural and urban areas. Study participants were selected by multistage sampling method. Data collection was done by a pre-tested and semi-structured questionnaire. Results: Among 400 study participants, 91% in urban and 60% in rural areas showed positive health seeking behaviour. In both areas, most of them preferred public health facilities. Major factor affecting health seeking behaviour in rural area was convenience of approach, while that in urban area was low cost of treatment. Majority rural population was unaware of health insurance policies, while almost half of urban population were aware of it. Conclusion: Positive health seeking behaviour and awareness on health insurance policies are seen more in urban area than rural. Awareness programmes on positive health seeking behaviour and health insurance are essential, especially in rural areas.